(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In recent years, high-strength concrete (HSC) has been widely applied as an excellent material for civil and infrastructure engineering. Although HSC has significant advantages in strength and durability, many studies have indicated that the elevated temperature deteriorates the compressive strength, tensile strength, elastic modulus and even durability of HSC. HSC has wide applications in the pre-stressed bridges, cable stayed bridges, long span bridges etc. It allows for the greater span for concrete girders than that with the normal strength concrete. The HSC enhance the girder capacities and ultimately reduces the number of girders. Thus, it is economical to use HSC in the projects where strength required is more. In this paper we used manufactured sand with partial replacement of mineral admixture such as silica fume, and GGBS for experimental work and results are obtain after curing.